1995
DOI: 10.1017/s0890037x00024179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional and Alternative Nursery Weed Management Strategies

Abstract: Soil cultivation (3 to 5 times/yr) and herbicide management (oxadiazon, 3.92 kg ai/ha), agricultural standards for reducing weed competition, were compared to three alternative nursery field management systems regarding weed suppression: ‘Norcen’ bird's-foot trefoil companion crop, ‘Wheeler’ winter rye cover crop/mulch, and grass sod (80% ‘Eton’ perennial ryegrass and 20% ‘Ruby’ red fescue). Field management treatment had a significant effect on observed weed populations. Weed densities were also subject to ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Living mulches may reduce soil water evaporation and increase infiltration (Calkins & Swanson, 1998). Within this experiment, soil moisture levels remained lower in the conventional treatment than in all other treatments that were monitored from 8 July until the end of the growing season in 1997.…”
Section: Inter-specific Competitionmentioning
confidence: 80%
“…Living mulches may reduce soil water evaporation and increase infiltration (Calkins & Swanson, 1998). Within this experiment, soil moisture levels remained lower in the conventional treatment than in all other treatments that were monitored from 8 July until the end of the growing season in 1997.…”
Section: Inter-specific Competitionmentioning
confidence: 80%
“…Interest in alternative and sustainable agricultural production systems that require fewer production inputs is growing (Calkins and Swanson 1995). The current emphasis on reduced pesticide use has led to increased interest in alternative weed management methods (Bellinder et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the state of Mississippi (USA) indicated that cover-crop residues, namely desiccated wheat, in notill systems reduced diurnal fluctuations in soil temperature rather than the mean temperatures, producing decreases in the maximums and increases in the minimums compared to conventional tillage systems (Dabney et al 2001). Calkins and Swanson (1998) showed that cover-crop effects on soil temperature in Minnesota (USA) were most dramatic near the soil surface, whereas the effects were moderated with increasing soil depth. On the ground, phytoseiid mites are likely to inhabit ground vegetation and/or upper soil layers, but not in deep soil layers.…”
Section: Discussionmentioning
confidence: 99%